2014
DOI: 10.1021/jp4112684
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activity and Stability of Lysozyme by Immobilization in the Matching Nanochannels of Mesoporous Silica Nanoparticles

Abstract: It is highly desirable to study the kinetics and spectroscopy of enzymes in a crowded and controllable microenvironment. In this work, we employ mesoporous silica of matching pore sizes to confine lysozyme in order to mimic enzyme in a crowded environment. The stability and activity of lysozyme immobilized in mesoporous silica nanoparticle (MSN) of various pore sizes were studied and correlated to spectroscopic data of the immobilized enzyme. By siteselective surface functionalization, we were able to avoid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 47 publications
4
88
0
Order By: Relevance
“…It was found that the confinement of lysozyme within 5.6 nm pores limited unfolding and hence increased the thermal stability of the protein. Additionally, this study showed superior catalytic activity by enzymes within the nanochannels as compared to those in the cytoplasm [58].…”
Section: Ph Sensitive Systemsmentioning
confidence: 61%
See 1 more Smart Citation
“…It was found that the confinement of lysozyme within 5.6 nm pores limited unfolding and hence increased the thermal stability of the protein. Additionally, this study showed superior catalytic activity by enzymes within the nanochannels as compared to those in the cytoplasm [58].…”
Section: Ph Sensitive Systemsmentioning
confidence: 61%
“…Kao et al devised a scheme to intentionally prevent this via opposing electrostatic interactions with site-selective surface functionalization, which allowed them to load lysozyme exclusively in the nanochannels [58]. Mesoporous silica nanoparticles were first functionalized with 3-aminopropyltriethoxysilane (APTES) such that the amines on the external surfaces became positively charged in a buffer solution at pH 3.2, giving the MSN surface a net positive charge.…”
Section: Ph Sensitive Systemsmentioning
confidence: 99%
“…In fact, the surfaces of colloidal MSNs have been successfully modified with the retention of their dispersibility by using various hydrophilic silylating agents, such as PEG-silane and amino- propyltriethoxysilane. 98,128,129,131,132,134,135 …”
Section: Compositional Control Of Msns (Incorporation Of Organic Groumentioning
confidence: 99%
“…54,170 In general, MSNs have been modified chemically to introduce functions, such as controlled release of drugs and catalysis. 135,171,172 For example, Nel et al prepared MSNs functionalized with supramolecular nanovalves that are tightly closed at physiological pH (7.4) but capable of opening and delivering drugs in acidifying cellular compartments. The β-cyclodextrin ring encircles the aromatic amines owing to their noncovalent bonding interactions under neutral pH conditions, and effectively blocks the opening of the pores and traps introduced drugs (Figure 17).…”
Section: Functionalization Of Msns For Their Practical Usementioning
confidence: 99%
“…Instead, a trend toward larger pore MSNs, HMSNs, and other pore-expanded MSNs that are capable of delivering larger compounds for genetic or peptide therapy applications have been shown to be more effective in targeting cancer resistant cells [462]. With pore expansion techniques, as those mentioned earlier with TMB, delivery of larger proteins [383,[463][464][465] and even genetic material [207,391] are possible.…”
Section: Drug Deliverymentioning
confidence: 99%